Islamization of science from the perspective of Ismail Raji al-faruqi - Nur Azizah Lubis; Hakmi Wahyudi; Rudiadi Rudiadi (Program Pascasarjana Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
The orientation of this article is to discuss the Islamization of science from the perspective of Ismail Raji al-Faruq. Humans living in this world have a desire to seek knowledge and truth. Knowledge is the result of a human effort to know. Knowledge in the narrow sense is a correct and definite decision. In the matter of science, humans must first understand what science is, what the obligations regarding science itself are. Even to the glory of science, humans must know it so that a sense of compulsory learning arises. In this day and age, we live in the modern era, we are obliged to study science in order to keep up with the times, because in fact science can reach the truth at the level of probability or possibility. Finding the truth is not easy and can be dangerous, but it is even more dangerous if we assume that the absolute truth is already in our hands. One of the pioneers of the Islamization of science is Ismail Raji AL-Faruqi, this simple article will attempt to explain how Ismail Raji al-Faruqi thinks about the Islamization of science. The method used is reviewing books and journals.